The Role of Kapitan Jonkers in Rejecting Racism From the VOC Policy in Marunda (1684-1689) - Ardiansyah; Jumardi (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2022)
Kapitan Jonkers had a confidant of leadership in the VOC. He rejected the policy of segregation between the tribes living in Marunda because some of his troops came from different ethnic groups and tribes. The problem of this research is how is Kapitan Jonkers' efforts to reject racist policies in Marunda?. The purpose of this research is to garner his heroism in opposing the concept of racism that has been instilled in the archipelago for a long time. The research method used is the historical method. The results of this study indicate that Kapitan Jonkers seeks to unite the ethnic groups living in the Marunda area. His rejection of the policy of inter-ethnic separation in Marunda is proof that Kapitan Jonkers is a person who struggles for inter-ethnic unity considering that most of his followers come from various regions in the archipelago. The division of each tribe and ethnicity in Marunda, according to him, can cause jealousy with each other so that divisions can occur between the tribes who live there.